Taiwan’s COVID-19 Success: A Lifeline for its Higher Education Sector? (Comparative & International Education Series, 2021)
Taiwan’s unparalleled success in preventing and containing the COVID-19 outbreak within its borders has drawn unprecedented international attention and recognition. This achievement presents many important prospects for Taiwan to counter escalating diplomatic isolation from the increasingly hardline governance of China’s Xi Jinping. Taiwan’s feat in crisis management also opens a critical window of opportunity to increase mutual cooperation with the international community. Particularly with regard to Taiwan’s higher education sector, this is a moment not to be missed.  Taiwan’s universities are facing seemingly insurmountable obstacles in the coming decade as university student populations are expected drop by 40%, due in part to Taiwan’s declining birth rate. This article explores the potential for Taiwan to capitalize on its COVID-19 success and soft power diplomacy by attracting students internationally to strengthen its higher education sector and thereby further bolster its reputation and prestige in the global community.How to Cite:Layman, E. W., & Nachman, L. (2022). Taiwan's COVID-19 success: A lifeline for its higher education ector? In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 11-24). STAR Scholars. https://starscholars.org/product/global-education/